PENGARUH PENAMBAHAN AIR LAUT TERHADAP PERUBAHAN ARUS LISTRIK DAN KEKERUHAN PADA PENGOLAHAN AIR LIMBAH INDUSTRI SECARA ELEKTROKOAGULASI (Politeknik Negeri Jakarta, 2020)
In this research, electronics industry waste water has been processed into clean water. The study was conducted by flowing of 4.5 liters of waste water into the three cells of electrocoagulation process tank. Each cell is filled 1.5 liters of waste water without the addition of sea water. The electrocoagulation process is carried out at a voltage of 12 V and interval time for observation the change of current and the turbidity is done every 10 minutes. Subsequently, the same procedure was performed and added the sea water with variation of volume of 5, 10 and 15 mL. Measuring of current was done by amperemeter and turbidity by turbidimeter. The best conditions are recommended for use of 10 mL of sea water, 12 volt of voltage and 110 minutes for processing time. Under these conditions the current can be increased from 0.21 A to 1.52 A or equivalent 7.2 times to the initial current and then turbidity can be reduced from 44,10 NTU to 3.25 NTU NTU or equivalent to 92.63 %.